BENTUK PENYAJIAN KESENIAN MUSIK ZIKIR NAZAM DI DESA SENTEBANG KECAMATAN JAWAI KABUPATEN SAMBAS - Kensiwi Kameswari; Imam Ghozali; Chiristianli Yery Silaban (Universitas Tanjungpura, 2020)
AbstractKensiwi Kameswari, 2020. Forms of Presentment of the Art of Dhikr Nazam Music in Sentebang Village, Jawai District, Sambas Regency. A Thesis. Performing Arts Education Study Program, Department of Language and Art Education. University of Tanjungpura Pontianak. Supervisor I: Dr. Imam Ghozali, M.Pd.; Supervisor II: Chiristianly Yery Silaban, M.Sn. This research is driven by the uniqueness of the form of presentation of the Nazam dhikr, which is the movement of the rumba musicians while dancing and the typical Sambas Songket cloth (gold thread fabric) worn by the musicians. This study mainly discusses the form of presentation of Nazam dhikr music art in Sentebang Village, Jawai District, Sambas Regency. The method used in this research is descriptive in the form of qualitative research using an inductive descriptive approach. Data sources in this study are the local public figures and practitioners. The data in this study are in the form of descriptions and audiovisuals about the music of the Nazam dhikr and were validated using triangulation and extension of observation. The findings showed that the Nazam dhikr is presented using several attributes such as the stage, makeup, fashion, sound system, lighting, formation, and order of presentation. The order of presentation consists of opening by pronouncing ta'awudh basmalah, reading ila hadrotin mustofa, reading the surah al-Fatihah, reciting the Prophet's prayer, and closing by reading prayers. The formation consists of the players inside the house or outside which is usually housed in a tent called Tarub. From the results of this study, the researcher hoped that the young generation of Sentebang Village, Jawai District, and Sambas Regency will get to know and preserve the art culture of their local area.Keywords: Form of Presentment, Nazam dhikr, Sambas, Sentebang Village.